Question
upstudy study bank question image url

\begin{tabular}{l} Question 8 \\ Solve for \( x x^{2} \) \\ \( 7-\frac{18}{(6 x+4)^{-13}}+6=27 \) \\ Round to 3 decimal places \\ Rod your answer \\ \hline\end{tabular}

Ask by Elliott Reid. in Canada
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x \approx -0.830 \)

Solution

Solve the equation \( 7-\frac{18}{(6x+4)^{-13}}+6=27 \). Solve the equation by following steps: - step0: Solve for \(x\): \(7-\frac{18}{\left(6x+4\right)^{-13}}+6=27\) - step1: Find the domain: \(7-\frac{18}{\left(6x+4\right)^{-13}}+6=27,x\neq -\frac{2}{3}\) - step2: Simplify: \(13-18\left(6x+4\right)^{13}=27\) - step3: Move the expression to the left side: \(13-18\left(6x+4\right)^{13}-27=0\) - step4: Subtract the numbers: \(-14-18\left(6x+4\right)^{13}=0\) - step5: Rewrite the expression: \(-18\left(6x+4\right)^{13}=14\) - step6: Change the sign: \(18\left(6x+4\right)^{13}=-14\) - step7: Divide both sides: \(\frac{18\left(6x+4\right)^{13}}{18}=\frac{-14}{18}\) - step8: Divide the numbers: \(\left(6x+4\right)^{13}=-\frac{7}{9}\) - step9: Simplify the equation: \(\sqrt[13]{\left(6x+4\right)^{13}}=\sqrt[13]{-\frac{7}{9}}\) - step10: Calculate: \(6x+4=\sqrt[13]{-\frac{7}{9}}\) - step11: Simplify the root: \(6x+4=-\frac{\sqrt[13]{7\times 3^{11}}}{3}\) - step12: Move the constant to the right side: \(6x=-\frac{\sqrt[13]{7\times 3^{11}}}{3}-4\) - step13: Subtract the numbers: \(6x=-\frac{\sqrt[13]{7\times 3^{11}}+12}{3}\) - step14: Multiply by the reciprocal: \(6x\times \frac{1}{6}=-\frac{\sqrt[13]{7\times 3^{11}}+12}{3}\times \frac{1}{6}\) - step15: Multiply: \(x=-\frac{\sqrt[13]{7\times 3^{11}}+12}{18}\) - step16: Check if the solution is in the defined range: \(x=-\frac{\sqrt[13]{7\times 3^{11}}+12}{18},x\neq -\frac{2}{3}\) - step17: Find the intersection: \(x=-\frac{\sqrt[13]{7\times 3^{11}}+12}{18}\) The solution to the equation \(7-\frac{18}{(6x+4)^{-13}}+6=27\) is \(x \approx -0.830142\). Rounding to 3 decimal places, the answer is \(x \approx -0.830\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve for \( x x^{2} \) in the equation \( 7 - \frac{18}{(6x + 4)^{-13}} + 6 = 27 \), we first simplify the equation: 1. Combine like terms on the left: \( 13 - \frac{18}{(6x + 4)^{-13}} = 27 \). 2. Rearrange to isolate the fractional term: \(-\frac{18}{(6x + 4)^{-13}} = 27 - 13\) \(-\frac{18}{(6x + 4)^{-13}} = 14\). 3. Multiply both sides by \(-1\): \(\frac{18}{(6x + 4)^{-13}} = -14\). 4. To eliminate the fraction, multiply both sides by \((6x + 4)^{-13}\): \(18 = -14(6x + 4)^{-13}\). 5. Rearranging gives: \( (6x + 4)^{-13} = -\frac{18}{14} = -\frac{9}{7} \). This result indicates we have an error since the left-hand side cannot be negative. Let’s try solving it step-by-step instead: From our corrected approach, we re-solve to find \( x \): 1. Set up \( 7 + 6 - 27 = \frac{18}{(6x + 4)^{-13}} \). 2. Simplifying gives \( -14 = \frac{18}{(6x + 4)^{-13}} \). 3. Since \(-14\) is negative as mentioned, you typically avoid non-reality. Thus instead of a numerical evaluation, it seems there's a conceptual block needing clarification or re-writing the parameters provided. Therefore, recheck the equation for any omissions or ask for further insights to visualize the setups correctly for \(x\). Exploring alternative equations or interpretations can become handy too!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy